Pelaksanaan Kegiatan Berbagi Sembako dan Penyerahan Bantuan dalam Meningkatkan Kesejahteraan Masyarakat yang Membutuhkan - Rommy Hardyansah; Fitri Aulia Rahma; Muchammad Catur Rizky; Didit Darmawan; Ficky Aliansyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity was carried out targeting underprivileged communities who experience limitations in meeting basic daily needs, particularly food. The main problem faced by the community is the increasing cost of living that is not always balanced with the family's economic capacity. The goal of this activity is to help ease the burden on the community by distributing basic food aid while simultaneously increasing social awareness in the surrounding community. The method used is Participatory Learning and Action (PLA), an approach that involves active community participation in every stage of the activity. The implementation began with the identification of potential beneficiaries with community leaders, followed by discussions to determine priority needs, followed by distribution of basic food aid and evaluation of the activity with the community. The results of the activity showed that the basic food packages were successfully distributed to the beneficiaries. Based on the evaluation, the assistance provided was able to help meet the community's short-term food needs and achieved a high level of participant satisfaction. In addition to providing economic benefits, this activity also strengthened social ties between the implementers and the community through active involvement in the entire series of activities. Thus, the community service activity through the distribution of basic food aid made a positive contribution to helping meet the community's basic needs and increasing social awareness and solidarity within the community.